Comparing Between Different Impressions Materials and Techniques for the Accuracy of Implant Position Transfer - Ahmed Abduljawad Ismail Alubaidi; Nagham H Kassab; Hasan Khiraldeen Mohialdeen (University of Mosul, College of Dentistry, 2024)
Aims: This study aimed to compare the accuracy of implant position transfer using three impression materials with two techniques. Materials and methods: A master model was fabricated with two parallel dental implants at the first and second premolars missing regions in size (4.0mm in diameter and 10mm in length); Two traditional impression techniques (open and closed tray); Three silicone impression materials were used which are: Condensation, Additional (heavy and low) and Additional (medium) consistencies. Sixty conventional impressions were taken, ten impressions for each material and each technique. The linear distance measurements were performed using two methods: Digital Vernier and Digital measurement by using Medit Intraoral Scanner. Results: The open tray technique showed significantly fewer changes (P≤ 0.05) with linear distance measurements when compared to the control, while the closed tray technique showed significantly more changes (P≤ 0.05) with linear distance measurements when compared to the control. In comparing Medit Design and digital vernier as methods of measurement for both open and closed tray techniques; there was no significant difference in the accuracy of measurements for both of these two methods of measurement at a level of(P≤ 0.05). Conclusion: The additional silicone material is the best in its accuracy in transferring implant position for the (open and closed tray) conventional impression technique. The condensation silicone material is the worst in accuracy in transferring implant position for (open and closed tray) conventional impression technique. The open tray technique showed significantly more accuracy than the closed tray technique in transferring implant position in the traditional impression technique.